Implementation of electronic voting system using aadhaar - Bopparathi, Naresh; S, Rambabu; ArunaManjusha, K (International Journal of Engineering and Technology, 2018)
The present voting system in India is a time consuming process and not so secured. Our project proposes and implements a simple and secured method of polling vote using aadhaar information. Over a period of time there have been many improvisations in the field of voting which aim at increasing the flexibility, reliability, security, scalability and less time consumption to announce the results. In this system the user has to use his finger print to poll the vote.The fingerprints available in the aadhaar database are used for the candidature verification, which will be stored in the computer through which the further process is carried out. The voter need not carry his/her voter ID to the polling booth. A finger print module is used for accessing fingerprints. Once the user gives the finger print it will be compared with the existing data and if it is a genuine user it will be verified else the user is barred from voting and also if a user attempts to vote for the second time it will not be allowed. Once the voting process is finished the authoritative officer accesses the results immediately using a unique PIN provided to him.Â